Registros posicionais de protrusão e lateralidade em resinaacrílica à partir de diferentes posições iniciais - Zuim, Paulo Renato Junqueira [UNESP]; Siqueira, Marina Bonato [UNESP]; Garcia, Alício Rosalino [UNESP]; Carvalho, Karina Helga Turcio de [UNESP]; Rezende, Maria Cristina Rosifini Alves [UNESP] (My University, 2010)
The lateral movement presents a combination of lateral condylar and protrusive displacement on the non-working side. The objective os this study was to check the differences in the adjustment of the semiadjustable articulator starting from two different initial positions, centric relation an intercuspal position using positional records of rotusion and lateral movements in acrylic resin for the adjustment of condylar guidance as for ennett Angle. Twenty pacients dentate and assintomatic were recruited and their adjustment were performed in the semiadjustable articulator checking the differences among the studied groups, not finding statistically significant differences. Concludes that, in semiadjustable articulator adjustment, starting the montage in centric relation or intercuspal position, the results obtained for the condylar guidande and Bennett Angle aren´t statistically diferents, as well there is no difference in condylar guidance adjustment using lateral or protrusive records.

O movimento de lateralidade apresenta uma combinação de deslocamento condilar lateral e protrusivo no lado de não trabalho. O objetivo deste estudo foi verificar as diferenças do ajuste do articulador semi ajustável à partir de duas posições iniciais diferentes, relação cêntrica e máxima intercuspidação, a partir da utilização de registros posicionais de protrusão e lateralidade em resina acrílica, tanto para o ajuste do guia condilar quanto para o ângulo de Bennett. Foram empregados 20 pacientes dentados assintomáticos para os quais realizou-se o ajuste do articulador verificando-se as diferenças entre os grupos estudados, não se encontrando diferenças estatisticamente significantes. Conclui-se que, no ajuste do articulador, seja a partir de uma montagem inicial em Relação Central ou Máxima Intercuspidação, os resultados obtidos para guia condilar e ângulo de Bennett, não são estatisticamente diferentes; bem como não há diferença em ajustar o guia condilar empregando-se o registro de lateralidade ou protrusivo.
Positional records of protrusion and lateral movements in acrylic resin starting from differents initials positions
Keywords: Centric relation; Dental articulators; Jaw relation record; Relação central; Articuladores dentários; Registro da relação maxilomandibular